A new species of Cyrtodactylus Gray, 1826 (Squamata: Gekkonidae) from Khanh Hoa province, Southern Vietnam - van Tri, Ngo; Onn, Chan Kin (Zootaxa, 2010)
A new species of bent–toed gecko, Cyrtodactylus yangbayensis sp. nov. is described from the monsoon evergreen forests of Truong Son Mountain Range, Khanh Hoa province. It differs from all other species of Indo–Chinese Cyrtodactylus by having a mean SVL of 83.5 mm; dark spots and blotches on the head; no continuous nuchal loop; 6–8 precloacal pores in males arranged in a chevron; five or six dark brown, irregular, dorsal bands between limb insertions; 18–20 subdigital lamellae under first toe; 15–17 subdigital lamellae under fourth toe; and a median row of enlarged subcaudal scales.